Traditionelle und komplementäre medizinversorgung, die patienten mit einer covid-19-diagnose angewendet haben traditional and complementary medicines methods used by patients diagnosed with covid-19 - CAN GÜRKAN, ÖZLEM (My University, 2023)
AIM: This study aimed to determine traditional and complementary medicines (T&CM) methods used by patients before and after being diagnosed with COVID-19. METHODS: This descriptive cross-sectional study was carried out between 27 March 2021 and 2 July 2021, in the community health services unit of Düzce Province, Central District, in the western Black Sea region. 547 people participated in the study. Two forms prepared by the researchers, the \"Participant Identification Form\" and the \"Assessment Form for the Use of Traditional and Complementary Medicine Methods,\" were used to collect the data. RESULTS: Before the diagnosis of COVID-19, patients reported that they consumed the highest rate of medicinal plants (56.1%) and fruits (40.4%) and prayed (40.4%) to prevent disease. After the diagnosis of COVID-19, they stated that they consumed the highest percentage of medicinal plants (68.4%) and fruit (53.0%) and prayed (48.4%) to reduce disease symptoms. It was seen that herbal products/herbal mixtures (medicinal plants [p < 0.001], fruits [p < 0.001], and fruit vinegars [p < 0.001]), and T&CM methods such as supplements like C, E, D, and other vitamins (p < 0.001), prayer (p < 0.001), massage (p < 0.001), and apitherapy (p < 0.001) were found to be statistically significant after COVID-19 diagnosis compared to before. CONCLUSION: In this study, it was determined that the patients often used T&CM methods such as herbal products (especially medicinal plants and fruits) and prayer before and after COVID-19 diagnosis, and the use of these T&CM methods increased significantly after diagnosis. Ziel: Ziel dieser Studie war es, die traditionelle und komplementäre Medizinversorgung (TKM), die Patienten mit einer Covid-19-Diagnose sowohl vor, als auch nach der Diagnose angewendet haben, zu bestimmen. Methoden: Diese beschreibende Querschnittsstudie wurde zwischen dem 27. März und dem 2. Juli 2021 in der Einheit des öffentlichen Gesundheitswesens im Zentrum der Provinz Düzce, in der westlichen Schwarzmeerregion durchgeführt. An der Studie nahmen 547 Personen teil. Zur Erhebung der Daten wurden von den Forschern ein, \"Teilnehmeridentifizierungsformular\" und ein \"Bewertungsformular für die Anwendung traditioneller und komplementärer Medizinpraktiken\" verwendet. Befunde: Vor der Diagnose von Covid-19 gaben Patienten an, dass sie die höchste Rate an Kräutern (56.1%) und Früchten (40.4%) konsumierten und beteten (40.4%), um sich vor der Krankheit zu schützen. Sie gaben an, Kräuter (68.4%) und Früchte (53.0%) am häufigsten zu konsumieren und beteten (48.4%), die Krankheitssymptome nach der Diagnose von Covid-19 zu lindern. Es zeigt sich, dass die Zunahme von TKM -Methoden wie die Einnahme von pflanzlichen Produkten (Heilpflanzen (p < 0.001), Früchte (p < 0.001) und Fruchtessig (p < 0.001)), Gebet (p < 0.001), Vitamine C, E, D usw. (p < 0.001) , Massage (p < 0.001) und Apitherapie (p < 0.001) nach der Covid-19-Diagnose im Vergleich zu vor der Covid-19-Diagnose aus statistischer Sicht bedeutend ist. Ergebnis: Die Studie zeigt, es wurde festgestellt, dass die Patienten vor und nach der Diagnose von Covid-19 häufig TKM-Methode wie pflanzliche Produkte (insbesondere Heilpflanzen und Früchte) und Gebete verwendeten und die Verwendung dieser TKM-Methode nach der Diagnose signifikant zunahm.
Keywords: Tıp; Sağlık Bilimleri; Medicine; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ENTEGRE VE TAMAMLAYICI TIP; Clinical Medicine (MED); CLINICAL MEDICINE; INTEGRATIVE & COMPLEMENTARY MEDICINE; Tamamlayıcı ve Alternatif Tıp; Complementary and Alternative Medicine; COVID-19; Pandemic; Traditional and complementary medicine methods; COVID-19; Pandemic; Traditional and complementary medicine methods